2008
DOI: 10.5713/ajas.2008.60725
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Thermotolerance in Transgenic Orchardgrass Plants with DgHSP17.2 Gene

Abstract: To develop transgenic orchardgrass (Dactylis glomerata L.) resistant to high temperature, the recombinant DgHSP17.2 gene was introduced into orchardgrass plants using the Agrobacterium-mediated transformation method and expressed constitutively under the control of the CaMV 35S promoter. The results of genomic DNA PCR and Southern analysis showed a DNA band and hybridization signal on agarose gel and X-ray film in transgenic orchardgrass plants harboring the recombinant DgHSP17.2 gene, but a DNA band and hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Suppressing expression of hsp23 and hsp70 in the flesh fly Sarcophaga crassipalpis with RNAi profoundly affected temperature tolerance (Rinehart et al., ), as did dsRNA knockdown of hsp90 in planthoppers (Lu, Chen, Liu, & Zhou, ). Transgenic approaches are widely used in plants (Kim et al., ; Maruyama et al., ; Wahid et al., ). For example, Arabidopsis engineered with wheat chloroplast hsp26 transgenes was substantially more tolerant under continuous high temperature than wild‐type and produced seeds at high temperature having higher germination potential than the wild‐type plants (Chauhan, Khurana, Nijhavan, Khurana, & Khurana, ).…”
Section: Technical Advances Have Yielded Additional Insightsmentioning
confidence: 99%
“…Suppressing expression of hsp23 and hsp70 in the flesh fly Sarcophaga crassipalpis with RNAi profoundly affected temperature tolerance (Rinehart et al., ), as did dsRNA knockdown of hsp90 in planthoppers (Lu, Chen, Liu, & Zhou, ). Transgenic approaches are widely used in plants (Kim et al., ; Maruyama et al., ; Wahid et al., ). For example, Arabidopsis engineered with wheat chloroplast hsp26 transgenes was substantially more tolerant under continuous high temperature than wild‐type and produced seeds at high temperature having higher germination potential than the wild‐type plants (Chauhan, Khurana, Nijhavan, Khurana, & Khurana, ).…”
Section: Technical Advances Have Yielded Additional Insightsmentioning
confidence: 99%
“…However, Δsba1 cells overexpressing Dgp23 showed better cell growth and viability against heat treatments. Major molecular chaperones such as Hsp101 (Queitsch et al 2000), Hsp70 (Lee and Schöffl 1996), and small Hsp (Kim et al 1997) have been reported to confer thermotolerance, but co-chaperones have not been well characterized. Although transcription levels of Hsp90 co-chaperones Hop and FKBP are induced by heat stress (Zhang et al 2003;Aviezer-Hagai et al 2007), only FKBP has a chaperone property (Bose et al 1996), and FKBP20 overexpression in yeast showed thermotolerance (Nigam et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(Cho et al 2001). Heat shock protein (HSP) gene isolated from cocksfoot was transformed into embryogenic callus of cocksfoot by Agrobacterium method (Kim et al 2008). Based on a leaf disk assessment, this transgenic plant showed heat tolerance at 60 • C which was lethal for non-transgenic plants.…”
Section: Integration Of New Biotechnologies In Breeding Programsmentioning
confidence: 99%